1997
DOI: 10.1038/ki.1997.269
|View full text |Cite
|
Sign up to set email alerts
|

Plasma leptin is partly cleared by the kidney and is elevated in hemodialysis patients

Abstract: Leptin, the gene product of the ob gene, is important in the control of appetite in rodents and may have an important role in humans. The clearance of leptin from the circulation is unknown. As the leptin receptor is present in the kidney, we evaluated the role of the kidney in removing circulating leptin in humans. We measured leptin in aortic and renal vein plasma in 8 patients with intact renal function and 6 patients with impaired renal function who were undergoing elective cardiac catheterization. Renal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
167
2
6

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(181 citation statements)
references
References 28 publications
6
167
2
6
Order By: Relevance
“…We demonstrated that elevation in plasma leptin due to impaired renal function occurred independently of other metabolic and endocrinological factors. The kidney may play a physiological role in leptin clearance [23]. If the intact leptin molecules are accumulated due to renal failure, hyperleptinaemia might account, at least in part, for malnutrition of patients with chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that elevation in plasma leptin due to impaired renal function occurred independently of other metabolic and endocrinological factors. The kidney may play a physiological role in leptin clearance [23]. If the intact leptin molecules are accumulated due to renal failure, hyperleptinaemia might account, at least in part, for malnutrition of patients with chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Yapılan çalışmalar serum leptin düzeylerinin sağ-lıklı yetişkin ve çocuklarda olduğu gibi KBY hastalarında da VKİ ile anlamlı korelasyona sahip olduğunu göstermiştir (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) . Çalışmamızda, KBY hasta grubunda cinsiyet ayırımı yapmaksızın kontrol grubunda olduğu gibi VKİ ile serum leptin düzeyleri arasında anlamlı pozitif korelasyon olduğunu bulduk.…”
Section: Discussionunclassified
“…Leptinin büyük çoğunluğunun dolaşımda bağlı olmayan formda bulunması ve moleküler büyüklüğü sıradan sentetik diyaliz zarından geçemeyeceğini düşündürmektedir (23) . Bununla ilgili birçok çalışma hemodiyaliz ile leptin düzeylerinin azalmadığını göstermiştir (15,17,(24)(25)(26)(27) . Hemodiyaliz uygulanan hasta sayımız az olduğu için PD uygulananlarla leptin düzeyleri açısından istatistiksel bir karşılaştırma yapamadık.…”
Section: Prediyaliz Hasta Grubuunclassified
See 1 more Smart Citation
“…Leptin is freely fi ltered into glomerulus but with very little excretion in urine (2). This is probably because it is reabsorbed and destructed in tubules (3). Serum leptin level is higher in chronic renal failure, hemodialysis and CAPD patients compared to general population (4,5).…”
mentioning
confidence: 99%